NEUTRACUETICAL EVALUATION OF BOERHAVIA DIFFUSA L. - G. R., Juna Beegum; S., Sugunan V.; Beevy, S. Suhara (International Journal of Current Pharmaceutical Research, 2016)
Objective: Boerhavia diffusa a tropical herb has been a subject of keen interest in phytochemical and pharmacological research due to its excellent medicinal values. The stress and need for quality control and standardisation of medicinal preparations from plants is gaining more importance today in view of the commercialization of drug formulations. Methods: WHO recommends various physicochemical, proximate and nutritive standards so that uniformity in composition and effectiveness is maintained? All the analysis was done using standard protocols. Results: The nutraceutical evaluation of the plant gives an insight into its value as a medicinal as well as highly nutritious one, safe for consumption both as a medicine and as a natural source for antioxidant activities. Conclusion: Thus the present finding suggests that B. diffusa have a promising potential not only to cure ailments but to maintain a healthy life.